Student Assessment Feedback Effectiveness Model for Enhancing Teaching Method and Developing Academic Performance - Tawafak, Ragad M.; Awanis, Romli; Alsinani, Maryam Juma (IGI Global, 2019)
There is a need for several applications and technologies in the higher education institutions in Oman to improve faculty-student performance. This exploratory study investigates whetherintegrating student assessment feedback with e-learning through coursework program of full semester instruction may simultaneously enhance and develop academic performance. In the first phase, a systematic review of the existing literature was carried out to determine the suitable related e-learning articles; then, generate a model of e-learning designed with evaluation forms that can measure the suitability of the technology, for assessment issues. In this study, surveys were distributed to BUC College in Oman to assess their satisfaction. The findings of this article aid in the improvement of the teaching method environment, assessment mechanisms, and student learning outcomes.